Teaching Practicum in English Language Teaching (ELT): A Systematic Review - İbrahim Şahin (Ömer Gökhan Ulum, 2023)
As a three-handed social process including pre-service teachers, teacher educators from academia, and mentor teachers from schools of practice, teaching practicum, with its reflective and collaborative notions, has recently gained more interest in the field of English language teaching (ELT). In this regard, this systematic review aimed to find out recent research based on teaching practicum in ELT. Regarding the PRISMA guidelines and clear eligibility criteria, the review included a total of 24 research articles based on the ELT teaching practicum. Of the articles, the majority were qualitative studies and mostly conducted in EFL (English as a foreign language) contexts such as Türkiye and Indonesia. MAXQDA (v.2020) software-based content analysis was conducted to analyze data, and the findings were demonstrated via tables including themes, categories, and codes. The study concluded that teaching practicum has several professional (e.g., theoretical and practical awareness, classroom management, and reflective practice) and personal gains (e.g., positive beliefs and attitudes toward ELT, reflectivity, more interaction and communication, and self-confidence) for pre-service ELT teachers. On the other hand, the selected studies also stressed negative professional aspects (e.g., the incompatibility between theory and practice, lack of feedback, and inefficient mentoring) and personal (e.g., lack of reflectivity, adaptation problems, and lack of social contact). The review lastly included implications revealed by these studies to shed light on the issue of ELT practicum for supporting further research.